A survey of data multicast techniques, architectures, andalgorithms. - Mir, N.F (IEEE Communications magazine)
This article presents a survey of architectures, techniques, and algorithms for multicasting data in communication switching networks. We start with a broadcast architecture using a separate copy network and a routing network. A few versions of this idea using Delta and Benes networks exist. Another multicast architecture is a recycling network where internal nodes act as relay points, accept packets from the switching fabric, and recycle them back into the fabric after relabeling the packets. Next, we give an overview of a system that uses the Boolean splitting multicast algorithm. In this system a nonblocking self routing broadcast banyan copy network has been proposed. The network consists of several components including a running adder network to generate running sums of copy numbers specified in the headers of input packets. We then describe a multicasting technique presented for a different class of switching networks called deflection-routing networks. Finally, the idea of extending a nonblocking network to a three-dimensional structure consisting of multiple parallel planes is also presented. At the end of this article, we compare the efficiencies of the presented multicast architectures